Band Gap Modification of Tio2 Using Solid State Reaction with Hydrides in Argon Atmosphere - Sh. Al-Omary, Saad; A. Algharagholy, Laith; E. Al-Dokheily, Mohsin (International Journal of Engineering and Technology, 2018)
TiOx (x<2) nanoparticles have been synthesized by solid state reaction between as-prepared TiO2 nanoparticles and NaAlH4, KBH4 as a reducing agents in argon atmosphere at two temperature 600 oC and 850 oC .Â the X-ray diffraction patterns of reduced TiO2 shows a peak shift and broadening which attributed to the lattice contraction after reduction treatment. AFM images confirm that the surface roughness of reduced TiO2 were larger than unmodified TiO2 nanoparticles due to the formation of oxygen vacancies. UVâ€Vis spectroscopy measurements revealed that the reduced TiO2 nanoparticles have an absorption edge lies in the visible region from the electromagnetic radiations with lower band gap. EDS spectra indicate that the as-prepared and reduced TiO2 nanoparticles have a high degree of purity and the acquired results confirm formation nonstoichiometric (TiO2-x) with oxygen deficient.Â Â Â